Molybdenum disulfide nanoflower composite material loaded with copper particles as well as preparation method and application of molybdenum disulfide nanoflower composite material
By loading copper nanoparticles by photochemical deposition on molybdenum disulfide nanoflower material, the problems of copper nanoparticles loading and Cu2+ loss are solved, and efficient antibacterial performance and stability are achieved, which is suitable for the elimination of bacterial infections. disinfect.
Patent Information
- Application Number
- CN202411782983.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing technology is difficult to effectively load copper nanoparticles to the surface of molybdenum disulfide material, exert antibacterial effects while reducing Cu2+ loss. The effect of traditional antibiotics on bacterial diseases is reduced, resulting in the development of efficient, stable and low-cost antibacterial agents becoming a challenge. .
Photochemical deposition method is used to uniformly grow copper nanoparticles on molybdenum disulfide nanoflower material. Through ultrasonic mixing and photodeposition reaction, a molybdenum disulfide nanoflower composite material is formed with copper particles. The copper ions are regenerated in situ by photoelectrons, reducing loss and enhancing Bactericidal efficiency.
The molybdenum disulfide nanoflower composite material with efficient copper particles is realized, which significantly improves antibacterial properties, reduces the loss of copper ions, has fast and effective disinfection capabilities for harmful microorganisms, and maintains stability under visible light irradiation.
Smart Images

Figure CN119234826A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of harmful microorganism disinfecting materials, and specifically relates to a molybdenum disulfide nanoflower composite material loaded with copper particles, and a preparation method and application thereof. Background Art
[0002] Bacterial infection is a serious threat to human health. Every year, a large number of people die from infectious diseases such as bacterial pneumonia, bacterial sepsis and severe bacterial wound infection worldwide. The misuse or overuse of traditional antibiotics has made antibiotic treatment ineffective for these bacterial diseases, while greatly increasing the cost of treating bacterial diseases. Therefore, the development of an efficient, stable and low-cost antibacterial agent is an important issue facing us today.
[0003] In recent years, the high anticancer and antibacterial properties of new nanomaterials have received extensive attention in the biomedical field. Due to the influence of the shape and size of nanomaterials and their high specific surface area, the chemical and physical properties of these materials are very different from their volume. During the sterilization process, nanomaterials have sterilization mechanisms such as metal ion release, physical damage, and oxidative stress. They have the advantages of high efficiency, strong bactericidal ability, good durability, and less secondary pollution.
[0004] As an emerging semiconductor material, molybdenum disulfide (MoS2) exhibits many excellent properties, including strong visible light absorption, biocompatibility, fluorescence quenching properties, etc. Molybdenum disulfide is a typical transition metal chalcogenide, and its bandgap is between 1.2-1.9 eV depending on the size. The light response range can cover most of the visible light region and even the near-infrared region. Therefore, it has good application potential in photocatalytic hydrogen production, pollutant degradation, photocatalytic sterilization, etc. At the same time, molybdenum disulfide can also be used as a co-catalyst in combination with other antibacterial materials.
[0005] In addition, the modification and composite of nanomaterials is also one of the important development directions of new materials. Through the synergistic effect between its components, the stability of nanoparticles can be controlled, energy utilization can be improved, and material activity can be enhanced. Nanosilver (Ag) materials, which are widely used today, have significant effects in the field of sterilization and disinfection. However, Ag, as a precious metal material, has a relatively high cost. In comparison, transition metals are cheaper and easier to obtain, especially nanocopper (Cu) materials, which also perform well in antibacterial applications. Copper is one of the trace elements in the normal metabolism of the human body, and single Cu is also non-toxic. But Cu 2+ It is also easy to be lost in water. Therefore, how to design a simple and effective method to load copper nanoparticles onto the surface of molybdenum disulfide materials, while exerting the antibacterial effect of Cu and reducing Cu 2+ Loss of antimicrobial composite materials is a challenge. Summary of the invention
[0006] In view of the above-mentioned technical problems existing in the prior art, the purpose of this application is to provide a molybdenum disulfide nanoflower composite material loaded with copper particles and its preparation method and application. The present invention utilizes photochemical deposition to make copper nanoparticles grow uniformly on the prepared molybdenum disulfide nanomaterial, and the synergistic effect of the two improves the sterilization efficiency.
[0007] In order to achieve the above objectives, the following technical solutions are proposed: A method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material comprises the following steps: Step 1: Molybdenum salt and sulfur source are dissolved in ultrapure water, mixed evenly, and then alkali solution is added to adjust the pH to neutral. The resulting mixed solution is transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The high-pressure reactor is sealed and then placed in a 120-220 ° C oven for hydrothermal reaction for 12-30 h. After the reaction is completed, it is cooled to room temperature, centrifuged, washed, and dried to obtain a three-dimensional flower-like structure of molybdenum disulfide nanoflower material; Step 2: Ultrasonically disperse the molybdenum disulfide nanoflower material obtained in step 1 in ultrapure water, then add the copper ion solution to mix, transfer it into a photoreactor after ultrasonic mixing, maintain anaerobic conditions by nitrogen bubbling, inject the reducing solution under light and stirring, and continue stirring the reaction at room temperature for 60-120 minutes before ending the photodeposition reaction; wherein, the light source band is controlled to be the visible light band of 420-630 nm, and the light power is 100-400W; Step 3: After the reaction in step 2 is completed, the reaction solution is centrifuged to obtain a precipitate, which is washed with ultrapure water and anhydrous ethanol to remove residual salt, and then dried to obtain a molybdenum disulfide nanoflower composite material loaded with copper particles having a three-dimensional structure.
[0008] Furthermore, in step 1, the molar ratio of the molybdenum salt to the sulfur source is 1:1.5-4, preferably 1:2-2.5.
[0009] Furthermore, in step 1, the molybdenum salt is sodium molybdate or ammonium molybdate, the sulfur source is ammonium sulfide, thiourea, thiourea, thioacetamide or sodium thiosulfate, and the total molar concentration of the molybdenum salt and the sulfur source dissolved in ultrapure water is 0.1-1 mol / L, preferably 0.5-0.6 mol / L.
[0010] Furthermore, the alkali solution in step 1 is an aqueous solution of sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate.
[0011] Furthermore, the hydrothermal reaction temperature in step 1 is 180-200° C., and the reaction time is 20-25 h.
[0012] Furthermore, in step 2, the copper ions are provided by a copper salt, which is at least one of copper chloride, copper nitrate, copper phosphate, and copper acetate, and the mass ratio of the copper element in the copper salt to the molybdenum disulfide nanoflower material is 0.05-1:10, preferably 0.1-0.2:10.
[0013] Furthermore, the reducing agent in the reducing solution of step 2 is hydrazine, sodium borohydride, potassium borohydride or sodium sulfite, the molar ratio of the reducing agent to the copper salt is 8-12:1, and the concentration of the reducing solution is 0.01~0.1 mol / L.
[0014] The present invention also provides an antibacterial application of the molybdenum disulfide nanoflower composite material loaded with copper particles. Under visible light irradiation, the light source band is controlled to be a visible light band of 420-630 nm, and the power is 100-400W. The molybdenum disulfide nanoflower composite material loaded with copper particles is put into a water body where harmful bacteria exist, and the pH of the water body is adjusted to 7-8, so as to photocatalytically disinfect the harmful bacteria in the water body.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention utilizes the self-assembled three-dimensional flower-like structure of molybdenum disulfide nanosheets and adopts the room-temperature photochemical deposition method to anchor nano-scale copper particles, which effectively solves the problem that the nano-copper particles are small and easy to agglomerate, and makes the nano-copper highly dispersed in the molybdenum disulfide.
[0016] 2) The copper ions released by the copper particle-loaded molybdenum disulfide nanoflower composite material during the disinfection process can be regenerated in situ by photoelectrons, effectively reducing the loss of CuNPs; on the other hand, the recombination of photogenerated electron-hole pairs of molybdenum disulfide is inhibited, comprehensively strengthening the disinfection and sterilization performance of the material.
[0017] 3) The molybdenum disulfide nanoflower composite material loaded with copper particles prepared by the present invention is used for disinfecting harmful microorganisms. It can quickly and effectively inactivate harmful microorganisms in water under visible light irradiation, and has efficient bactericidal properties against a variety of bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the Cu / MoS2 composite functional material prepared in Example 1; Figure 2 This is the EDS image of the Cu / MoS2 composite functional material prepared in Example 1; Figure 3 XRD patterns of 2.0% Cu / MoS2 material and MoS2 material prepared in Example 1 and 10% Cu / MoS2 material prepared in Example 3; Figure 4This is a comparison chart of the disinfection effects of the Cu / MoS2 composite functional material or MoS2 prepared in Example 1 and a blank control under (a) light and (b) dark conditions.
[0019] Figure 5 This is a graph showing the results of a cyclic disinfection experiment of the copper-based molybdenum disulfide nanoflower composite functional material (2.0% Cu / MoS2) under light conditions in Example 1.
[0020] Figure 6 This is a comparison chart of the disinfection effects of the copper-loaded material systems with different proportions prepared in Examples 1, 2 and 3, as well as the MoS2 prepared in step 1) of Example 1 and the blank control under light conditions.
[0021] Figure 7 This is a comparison chart of the disinfection effects of 2% Cu / MoS2 copper-loaded materials prepared under different synthesis conditions in Example 1, Example 4 and Example 5, as well as a blank control under light conditions.
[0022] Figure 8 This is a SEM image of the Cu / MoS2 composite functional material prepared in Example 7; Fig. 9 This is a comparison chart of the agar plates of 2.0% Cu / MoS2 material prepared in Example 1 for different bacteria under different lighting conditions for different periods of time. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0024] Example 1 Preparation method and application of copper-based molybdenum disulfide nanoflower composite functional material for disinfecting harmful microorganisms, the steps are as follows Preparation of 2.0% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material, the steps are as follows: 1) Dissolve 2.47g (NH4)2MoO4 and 2.284g NH2CSNH2 in 70mL water in turn, stir for 30 min until completely mixed, and form 70mL of mixed solution A; adjust the pH of mixed solution A to 7.0 with 1 M NaOH solution to obtain solution B; transfer solution B to a 100mL autoclave with a polytetrafluoroethylene liner; seal the autoclave and transfer it to an oven, heat it to 200℃ and keep it for 24h, and take it out after cooling to room temperature to obtain a mixed solution C with precipitate; transfer mixed solution C to a centrifuge tube, centrifuge it at 8000 rpm for 5 min to obtain a black solid precipitate; wash the black solid with ultrapure water and anhydrous ethanol for 3 times to obtain a black solid material, and then place it in a vacuum oven at 60℃ for 8h to successfully obtain a molybdenum disulfide material MoS2 with a three-dimensional nanoflower-like structure; 2) Dissolve 5.3 mg CuCl2·2H2O in 5 mL ultrapure water, and obtain a uniform divalent copper ion solution after ultrasonic treatment for use; dissolve 12.4 mg NaBH4 in 5 mL ultrapure water, and obtain a uniform sodium borohydride solution after ultrasonic treatment for use; weigh 100 mg of the molybdenum disulfide material MoS2 prepared in step 1) and ultrasonically disperse it in 40 mL ultrapure water to obtain a molybdenum disulfide dispersion, add the above-prepared divalent copper ion solution, and ultrasonically mix; transfer the mixed solution to a quartz photoreactor (a stirring magnet is added to the photoreactor, and the photoreactor is placed on a magnetic stirrer, the same below), continue to bubbling nitrogen to remove oxygen in the reaction environment, maintain an oxygen-free atmosphere, control the reaction at room temperature by a constant temperature water bath, and maintain magnetic stirring; turn on the xenon lamp to keep the light wavelength at 420-630 nm, the illumination power of the xenon lamp is 300 W, and under a nitrogen atmosphere, the above-prepared sodium borohydride solution is slowly injected into the reactor with a syringe. The reaction is continued for 1 hour and then centrifuged. The obtained solid is washed with water and anhydrous ethanol for 3 times, and then dried in a vacuum oven at 60 °C to obtain the 2.0% Cu / MoS2 composite functional material with a three-dimensional nanoflower spherical structure.
[0025] The SEM image of the copper-based molybdenum disulfide nanoflower composite functional material prepared in Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the molybdenum disulfide material prepared in Example 1 is successfully self-assembled into a flower ball by nanosheets, and the diameter of the flower ball is about 0.5-3 μm. However, due to the small particle size and uniform dispersion of nano-copper, it cannot be directly observed from the SEM, so it is further confirmed by the EDS element spectrum ( Figure 2 ).from Figure 2It can be seen that the molybdenum disulfide material prepared in Example 1 is a flower ball structure, and the material is composed of Mo, S, and Cu elements, which successfully proves the existence of Cu. In the selected area, these elements are evenly distributed, proving the uniform distribution of Cu on the MoS2 flower ball sheet, and successfully realizing the loading of Cu on the material.
[0026] The XRD patterns of the 2.0% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material prepared in Example 1 and the molybdenum disulfide MoS2 prepared in step 1) of Example 1 are as follows: Figure 3 As shown in the figure, the peaks of MoS2 material are located at 14.21°, 33.74°, 39.5°, and 58.7°, corresponding to the (002), (100), (103), and (110) crystal planes of MoS2 material, respectively. At the same time, the test results of 2.0% Cu / MoS2 material show almost the same peaks, which proves the successful synthesis of MoS2 nanoflower material, and the introduction of Cu loading does not affect the basic structure of MoS2, but is scattered and anchored on the surface of MoS2.
[0027] Example 2 Preparation method and application of copper-based molybdenum disulfide nanoflower composite functional material for disinfecting harmful microorganisms, the steps are as follows Preparation of 1% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material, the steps are as follows: 1) preparing a molybdenum disulfide material having a three-dimensional nanoflower spherical structure according to the operation method of step 1) of Example 1; 2) Dissolve 2.7 mg CuCl2·2H2O in 5 mL ultrapure water, and obtain a uniform divalent copper ion solution after ultrasonic treatment for use; dissolve 6.2 mg NaBH4 in 5 mL ultrapure water, and obtain a uniform sodium borohydride solution after ultrasonic treatment for use; weigh 100 mg of the molybdenum disulfide material prepared in step 1) and ultrasonically disperse it in 40 mL ultrapure water to obtain a molybdenum disulfide dispersion, add the above-prepared divalent copper ion solution, and ultrasonically mix; transfer the mixed solution to a quartz photoreactor, continue nitrogen bubbling to remove oxygen in the reaction environment, maintain an anaerobic atmosphere, control the reaction at room temperature by a constant temperature water bath, and maintain magnetic stirring; turn on the xenon lamp to maintain the illumination wavelength of 420-630 nm, the illumination power of the xenon lamp is 300W, and slowly inject the above-prepared sodium borohydride solution into the reactor with a syringe in a nitrogen atmosphere. After the reaction lasts for 1 hour, centrifuge separation is performed, and the obtained solid is washed 3 times with water and anhydrous ethanol respectively, and then placed at 60 The 1.0% Cu / MoS2 composite functional material with a three-dimensional nano-flower spherical structure was obtained.
[0028] Example 3 Preparation method and application of copper-based molybdenum disulfide nanoflower composite functional material for disinfecting harmful microorganisms, the steps are as follows Preparation of 10% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material, the steps are as follows: 1) preparing a molybdenum disulfide material having a three-dimensional nanoflower spherical structure according to the operation method of step 1) of Example 1; 2) Dissolve 26.6 mg CuCl2·2H2O in 5 mL ultrapure water, and obtain a uniform divalent copper ion solution after ultrasonic treatment for use; dissolve 62.1 mg NaBH4 in 5 mL ultrapure water, and obtain a uniform sodium borohydride solution after ultrasonic treatment for use; weigh 100 mg of the molybdenum disulfide material prepared in step 1) and ultrasonically disperse it in 40 mL ultrapure water to obtain a molybdenum disulfide dispersion, add the above-prepared divalent copper ion solution, and ultrasonically mix; transfer the mixed solution to a quartz photoreactor, continue nitrogen bubbling to remove oxygen in the reaction environment, maintain an anaerobic atmosphere, control the reaction at room temperature by a constant temperature water bath, and maintain magnetic stirring; turn on the xenon lamp to maintain the illumination wavelength of 420-630 nm, the illumination power of the xenon lamp is 300W, and slowly inject the above-prepared sodium borohydride solution into the reactor with a syringe in a nitrogen atmosphere. After the reaction lasts for 1 hour, centrifuge separation is performed, and the obtained solid is washed 3 times with water and anhydrous ethanol respectively, and then placed at 60 The 10% Cu / MoS2 composite functional material with a three-dimensional nano-flower spherical structure was obtained.
[0029] The XRD pattern of the 10% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material prepared in Example 3 is as follows Figure 3 As shown, the test results show almost the same peaks as the MoS2 material in Example 1, which proves that the method achieves the introduction of Cu loading without affecting the basic structure of molybdenum disulfide.
[0030] Example 4 Preparation method and application of copper-based molybdenum disulfide nanosheet composite functional material for disinfecting harmful microorganisms, the steps are as follows The steps for preparing 2% Cu / MoS2 copper-based molybdenum disulfide nanosheet composite functional material are as follows: 5.3 mg CuCl2·2H2O was dissolved in 5 mL ultrapure water, and a uniform divalent copper ion solution was obtained after ultrasonic treatment for standby use; 12.4 mg NaBH4 was dissolved in 5 mL ultrapure water, and a uniform sodium borohydride solution was obtained after ultrasonic treatment for standby use; 100 mg of molybdenum disulfide nanosheet material commercially available from Aladdin was ultrasonically dispersed in 40 mL ultrapure water to obtain a molybdenum disulfide dispersion, and the above-prepared divalent copper ion solution was added and ultrasonically mixed; the mixed solution was transferred to a quartz photoreactor, and nitrogen bubbling was continued to remove oxygen from the reaction environment to maintain an anaerobic atmosphere. The reaction was controlled to proceed at room temperature by a constant temperature water bath, and magnetic stirring was maintained; the xenon lamp was turned on to maintain the illumination wavelength of 420-630 nm, and the illumination power of the xenon lamp was 300 W. In a nitrogen atmosphere, the above-prepared sodium borohydride solution was slowly injected into the reactor with a syringe, and the reaction lasted for 1 hour before centrifugation. The obtained solid was washed 3 times with water and anhydrous ethanol respectively, and then placed at 60 ℃ vacuum oven to obtain the 2.0% Cu / MoS2 copper-based molybdenum disulfide nanosheet composite functional material.
[0031] Example 5 Preparation method and application of copper-based molybdenum disulfide nanoflower composite functional material for disinfecting harmful microorganisms, the steps are as follows The steps for preparing a 2% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material without adding a reducing agent are as follows: 1) preparing a molybdenum disulfide material having a three-dimensional nanoflower spherical structure according to the operation method of step 1) of Example 1; 2) Dissolve 5.3 mg CuCl2·2H2O in 5 mL ultrapure water, and obtain a uniform divalent copper ion solution after ultrasonic treatment for later use; weigh 100 mg of the molybdenum disulfide material prepared in step 1) and ultrasonically disperse it in 40 mL ultrapure water to obtain a molybdenum disulfide dispersion, add the above-prepared divalent copper ion solution, and ultrasonically mix; transfer the mixed solution to a quartz photoreactor, continue nitrogen bubbling to remove oxygen in the reaction environment, maintain an anaerobic atmosphere, control the reaction at room temperature by a constant temperature water bath, and maintain magnetic stirring; turn on the xenon lamp to maintain the illumination wavelength at 420-630 nm, the illumination power of the xenon lamp is 300 W, and in a nitrogen atmosphere, slowly inject 5 mL of methanol into the reactor with a syringe. After the reaction lasts for 1 hour, centrifugal separation is performed, and the obtained solid is washed with water and anhydrous ethanol for 3 times, respectively, and then placed in a 60°C vacuum oven to dry to obtain the 2% Cu / MoS2 composite functional material with a three-dimensional nanoflower spherical structure.
[0032] Application Example 1: Different catalyst materials are used to disinfect harmful bacteria. The specific process is as follows: S1: Prepared at a concentration of 10 8 CFU / mL of Escherichia coli suspension; S2: Take 20 mL of the prepared PBS buffer solution (pH = 7.4), add 0.004 g of 2.0% Cu / MoS2 or molybdenum disulfide MoS2 prepared in Example 1, disperse the catalyst in the solution by ultrasound, stir magnetically, control the reaction environment to room temperature 25 ° C in a constant temperature water bath, add 200 μL of 10 8 CFU / mL of Escherichia coli suspension, the initial concentration of Escherichia coli in the mixture is 10 6 CFU / mL, a multiphase catalytic water disinfection reaction was carried out on Escherichia coli in the dark or light conditions (the light conditions were: turning on the xenon lamp light source, the light source band was controlled by optical components to be the visible light band of 420-630nm, and the light power was 300W), the sampling frequency was 15 minutes each time, and the reaction was carried out for a total of 90 minutes.
[0033] The operation steps of sampling analysis are as follows: take 1 mL of the sample in step S2 above and immediately add it to 9 mL of PBS buffer solution. After mixing evenly, take 1 mL from the mixed solution and add it to 9 mL of PBS buffer solution. Dilute the reaction solution step by step to the appropriate multiple. Take 0.1 mL of the final diluted reaction solution and evenly spread it on the agar plate. Put the agar plate in an incubator and incubate it at 37 °C for 24 h. Check and count the number of colonies.
[0034] In addition, a blank control experiment was set up, and the experimental conditions repeated the harmful bacteria elimination process of the above steps S1 and S2, with the only difference being that "no catalyst was added".
[0035] According to the above experimental conditions, the materials prepared in Examples 1-5 were used as catalyst materials for performance testing, and the experimental results are as follows: 1) Different catalyst materials were used in the harmful bacteria disinfecting experiment. The 2.0% Cu / MoS2 and MoS2 prepared in Example 1 were used as catalyst materials, and the blank control without adding catalyst was used. The disinfecting results of Escherichia coli under dark and light conditions were summarized in Figure 4 As shown in sub-picture a and sub-picture b. Figure 4 The following conclusions can be drawn: First, after 90 minutes of reaction, under light conditions, 2.0% Cu / MoS2 can increase the inactivation rate of Escherichia coli in water from 61.7% in dark conditions to 100%, proving that light conditions can significantly improve the catalytic performance of molybdenum disulfide materials, and the introduction of Cu enhances the photocatalytic sterilization performance of molybdenum disulfide materials. After the disinfection reaction was completed under light conditions, the water was filtered through a 0.45-micron pore to prepare samples, and ICP-OES was used to test the copper ion leakage, and no copper ion was detected at the ppm level.
[0036] Second, pure MoS2 has a low inactivation effect on Escherichia coli due to simple physical particle collisions in a dark system. After 90 minutes of illumination, the MoS2 material can achieve a 64.8% inactivation rate on Escherichia coli in simulated water, indicating that the molybdenum disulfide material has a good light response effect.
[0037] 2) A cyclic experimental test of the 2.0% Cu / MoS2 material of Example 1 was also carried out. The experimental conditions repeated the harmful bacteria disinfecting process of the above steps S1 and S2 under light conditions, with the difference that after each reaction for 90 minutes, the recovered 2.0% Cu / MoS2 material was used to carry out the next Escherichia coli disinfecting experiment. The specific steps of material recovery are: centrifuging the material in the residual liquid, washing it alternately with ultrapure water and anhydrous ethanol, and drying it to obtain the recovered material. According to the above experimental process, the results of the cyclic experiment of 2.0% Cu / MoS2 for efficient disinfecting of harmful bacteria under light conditions are shown as follows. Figure 5 The logarithmic survival of bacteria in the 5-cycle antibacterial experiment is shown in Figure 5 As shown in the figure, the disinfection performance of 2.0% Cu / MoS2 maintained good stability. After 5 cycles, it can still disinfect bacteria with an initial bacterial density of 10 6 CFU / mL of Escherichia coli suspension achieved a bactericidal efficiency of 94%.
[0038] 3) In addition, the comparison chart of the killing effect of the blank control without any catalyst, MoS2 and 2.0% Cu / MoS2 prepared in Example 1, 1% Cu / MoS2 prepared in Example 2, and 10% Cu / MoS2 prepared in Example 3 under the control of light conditions is summarized in Figure 6 In. From Figure 6 It can be seen that: First, the 1% Cu / MoS2 material prepared in Example 2 had a 90.9% inactivation rate against Escherichia coli in simulated water in 90 minutes. After the test reaction, the water was filtered through a 0.45 micron pore to prepare a sample, and the copper ion leakage was tested by ICP-OES, and no copper ion was detected at the ppm level.
[0039] Second, the 2.0% Cu / MoS2 material prepared in Example 1 and the 1% Cu / MoS2 material prepared in Example 2 have the best disinfecting effect on Escherichia coli under light.
[0040] Third, the 10% Cu / MoS2 material prepared in Example 3 had an inactivation rate of 87.7% on Escherichia coli in simulated water in 90 minutes. After the test reaction, the water was filtered through a 0.45 micron pore to prepare a sample. The copper ion seepage was tested by ICP-OES, and the copper ion was detected to be 0.1 mg L at the ppm level. -1 .
[0041] according to Figure 6 The comparison results of the disinfecting effect on the target harmful microorganism Escherichia coli show that: under light excitation, when other conditions are the same, different materials show different efficiencies in disinfecting Escherichia coli. The Cu / MoS2 composite material has better disinfecting performance than pure MoS2 material, and has a good antibacterial effect within a reaction time of 90 minutes. It can also stably control copper and reduce the loss of copper in the reaction, making the material sustainable. At the same time, different ratios of Cu / MoS2 composite functional materials also show different efficiencies in disinfecting Escherichia coli, and the disinfecting performance is best when the Cu loading is 2 wt%.
[0042] 4) In addition, the 2% Cu / MoS2 copper-loaded materials prepared under different synthesis conditions in Examples 1, 4 and 5, as well as the blank control, were respectively used under light to disinfect the target harmful microorganism Escherichia coli. The results are summarized in Figure 7 In, from Figure 7 It can be seen that: First, the 2% Cu / MoS2 material prepared in Example 4 had a 79.8% inactivation rate against Escherichia coli in simulated water in 90 minutes. After the test reaction, the water was filtered through a 0.45 micron pore to prepare a sample, and the copper ion leakage was tested by ICP-OES, and no copper ion was detected at the ppm level.
[0043] Second, the 2% Cu / MoS2 material prepared in Example 5 had a 92.6% inactivation rate against Escherichia coli in simulated water in 90 minutes. The water after the test reaction was filtered through a 0.45 micron pore and the result was 0.1 mg L at the ppm level. -1 .
[0044] Figure 7 The comparative results of the disinfecting effect on the target harmful microorganism Escherichia coli show that: under light excitation, when other conditions are the same, different materials show different efficiencies in disinfecting Escherichia coli. The material with the morphology of nanoflower balls has better disinfecting performance than the nanosheet material, and has a good antibacterial effect within a reaction time of 90 minutes. At the same time, the material in Example 1 with the addition of a reducing agent has a better disinfecting effect and less copper loss than the material in Example 5 without the addition of a reducing agent. The embodiment shows that multi-component composite is an effective means to improve the disinfecting and sterilization function of materials through the synergistic effect of multi-component materials, and the materials are stable, sustainable and recyclable.
[0045] Application Example 2: The 2% Cu / MoS2 material prepared in Example 1 is used to disinfect different harmful microorganisms. The construction of the disinfecting reaction system and the analysis and testing operation process are the same as those in Application Example 1. The only difference is that "the Escherichia coli suspension in step S1 is replaced by a bacterial suspension of Staphylococcus aureus or Pseudomonas aeruginosa of the same concentration", and the rest of the steps are the same. The agar plate comparison of the test results of disinfecting different harmful microorganisms under light conditions over time is shown in the figure below. Fig. 9 As shown in the figure, after 45 minutes of reaction, the three bacteria were all disinfected with good effect. After 90 minutes, the disinfecting rate of Staphylococcus aureus and Escherichia coli reached 100%, and the disinfecting rate of Pseudomonas aeruginosa was as high as 98%, indicating that the copper-based molybdenum disulfide nanoflower composite functional material has good broad-spectrum bactericidal properties and can be used in a wide range of applications.
[0046] Example 6 Preparation method and application of copper-based molybdenum disulfide nanoflower composite functional material for disinfecting harmful microorganisms, the steps are as follows The 2% Cu / MoS2 copper-based molybdenum disulfide nanoflower composite functional material was prepared under light-free conditions. The steps are as follows: 1) preparing a molybdenum disulfide material having a three-dimensional nanoflower spherical structure according to the operation method of step 1) of Example 1; 2) A 2% Cu / MoS2 composite functional material having a three-dimensional nanoflower spherical structure was prepared according to the operating method of step 2) of Example 1, except that the xenon lamp light source was not turned on and the process was carried out in the absence of light.
[0047] The copper-based molybdenum disulfide composite functional material prepared in Example 6 was subjected to a harmful bacteria disinfecting experiment under light using the operating conditions of steps S1-S2 of Example 1. After 90 minutes, the inactivation rate of Escherichia coli in the water reached 91.7%. The copper ion leakage was tested by ICP-OES, and the detection level at ppm was 0.1 mg L -1 .
[0048] Example 7 Preparation method and application of copper-based molybdenum disulfide composite functional material for disinfecting harmful microorganisms, the steps are as follows The 2% Cu / MoS2 copper-based molybdenum disulfide composite functional material was prepared by changing the raw material source, and the steps are as follows: 1) Molybdenum disulfide material was prepared according to the operation method of step 1) of Example 1, except that "(NH4)2MoO4 was replaced by Na2MoO4 in an equal molar ratio", and other conditions remained unchanged, and finally molybdenum disulfide material was obtained.
[0049] 2) Prepare a 2% Cu / MoS2 copper-based molybdenum disulfide composite functional material according to the operating method of step 2) of Example 1, the only difference being that "100 mg of molybdenum disulfide is replaced by 100 mg of molybdenum disulfide material prepared in step 1) of Example 7", and the other conditions remain unchanged, and finally obtain a 2% Cu / MoS2 copper-based molybdenum disulfide composite functional material.
[0050] The SEM image of the copper-based molybdenum disulfide composite functional material prepared in Example 7 is as follows: Figure 8 As shown. Figure 8 It can be seen that the molybdenum disulfide material prepared in Example 7 is a strip structure at the nanoscale.
[0051] The copper-based molybdenum disulfide composite functional material prepared in Example 7 was subjected to a harmful bacteria disinfecting experiment under light using the operating conditions of steps S1-S2 of Example 1. After 90 minutes, the inactivation rate of Escherichia coli in the water reached 86.8%. ICP-OES was used to test the copper ion leakage, and no copper ion was detected at the ppm level.
[0052] The copper ion leakage of Examples 1-7 illustrates that it is the combined effect of photoelectrons and reducing agents that enables copper ions to be stably anchored on the surface of molybdenum disulfide. The reason is that the photoelectrons originate from the surface of the molybdenum disulfide material, which helps to reduce copper in situ under surface coordination. The Cu atoms loaded on the molybdenum disulfide nanoflowers are more stably anchored, which can effectively prevent the leakage of copper ions in the water during photocatalytic disinfection of harmful bacteria in the water.
[0053] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material, characterized in that The steps include: Step 1: Molybdenum salt and sulfur source are dissolved in ultrapure water, mixed evenly, and then alkali solution is added to adjust the pH to neutral. The resulting mixed solution is transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The high-pressure reactor is sealed and then placed in a 120-220 ° C oven for hydrothermal reaction for 12-30 h. After the reaction is completed, it is cooled to room temperature, centrifuged, washed, and dried to obtain a three-dimensional flower-like structure of molybdenum disulfide nanoflower material; Step 2: Ultrasonically disperse the molybdenum disulfide nanoflower material obtained in step 1 in ultrapure water, then add the copper ion solution to mix, transfer it into a photoreactor after ultrasonic mixing, maintain anaerobic conditions by nitrogen bubbling, inject the reducing solution under light and stirring, and continue stirring the reaction at room temperature for 60-120 minutes before ending the photodeposition reaction; wherein, the light source band is controlled to be the visible light band of 420-630 nm, and the light power is 100-400W; Step 3: After the reaction in step 2 is completed, the reaction solution is centrifuged to obtain a precipitate, which is washed with ultrapure water and anhydrous ethanol to remove residual salt, and then dried to obtain a molybdenum disulfide nanoflower composite material loaded with copper particles having a three-dimensional structure.
2. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that In step 1, the molar ratio of the molybdenum salt to the sulfur source is 1:1.5-4.
3. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that In step 1, the molybdenum salt is sodium molybdate or ammonium molybdate, the sulfur source is ammonium sulfide, thiourea, thiourea, thioacetamide or sodium thiosulfate, and the total molar concentration of the molybdenum salt and the sulfur source dissolved in ultrapure water is 0.1-1 mol / L.
4. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that The alkali solution in step 1 is an aqueous solution of sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate.
5. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that The hydrothermal reaction temperature of step 1 is 180-200°C, and the reaction time is 20-25h.
6. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that In step 2, the copper ions are provided by a copper salt, which is at least one of copper chloride, copper nitrate, copper phosphate, and copper acetate. The mass ratio of the copper element in the copper salt to the molybdenum disulfide nanoflower material is 0.05-1:
10.
7. The method for preparing a copper particle-loaded molybdenum disulfide nanoflower composite material according to claim 1, characterized in that The reducing agent in the reducing solution of step 2 is hydrazine, sodium borohydride, potassium borohydride or sodium sulfite, the molar ratio of the reducing agent to the copper salt is 8-12:1, and the concentration of the reducing solution is 0.01~0.1 mol / L.
8. A molybdenum disulfide nanoflower composite material loaded with copper particles prepared by the method as described in any one of claims 1 to 7.
9. Antibacterial application of the molybdenum disulfide nanoflower composite material loaded with copper particles as claimed in claim 8.
10. The use according to claim 9, characterized in that Under visible light irradiation, the light source band is controlled to be 420-630 nm in the visible light band, and the power is 100-400W. The molybdenum disulfide nanoflower composite material loaded with copper particles is put into a water body containing harmful bacteria, and the pH of the water body is adjusted to 7-8 to photocatalytically disinfect the harmful bacteria in the water body.
Citation Information
Patent Citations
Hydrothermal preparation method of flower-shaped molybdenum disulfide / copper oxide composite nano material
CN106732668A
Copper nanoparticle / molybdenum disulfide composite material and preparation method and application thereof
CN113647411A
Composite nano material as well as preparation method and application thereof
CN114772643A
Copper particle loaded sulfur zinc indium composite material and preparation method and application thereof
CN115739119A
Biochar coupled copper catalyst and preparation method and application thereof
CN115770572A
Cited By
Method for preparing metal particle highly-dispersed anchoring catalyst based on photo-thermal coupling subcritical technology and application
CN119425739A
